Tranexamic acid for post-partum haemorrhage in the WOMAN trial - Miller, Suellen (2017)
As clinicians and researchers of post-partum haemorrhage, we appreciate the clinical trial of tranexamic acid1 and applaud the researchers and results. We want to emphasise the importance of the addition of tranexamic acid to other technologies and strategies to form a complete comprehensive package for post-partum haemorrhage (or emergency post-partum haemorrhage bundle),2 which begins at the community level and proceeds, with attention to context, through primary health care to the referral-hospital level. As the authors note, tranexamic acid was tested at higher-level facilities (ie, secondary and tertiary hospitals) with providers not only able to give intravenous injections, but who were skilled enough (and equipped) to deliver a 1 mL/min dose of 1 g tranexamic acid, do hysterectomy or laparotomy, and give blood transfusions. Furthermore, the findings suggested early (<3 h) treatment with tranexamic acid, which is not always possible given the distances and delays women face in the settings of the community or primary health care. It could be some time before the bioavailability and correct dose of alternative routes have been trialled. For now in the setting of the community or primary health care, in which intravenous injections are neither safe nor feasible, and in higher-level facilities, in which a woman could arrive more than 3 h after the haemorrhage starts, a comprehensive continuum of care for post-partum haemorrhage is needed.3 At lower-level health-care facilities (ie, primary health care and dispensaries) the uterine balloon tamponade (as a packaged kit)4 and non-pneumatic antishock garment5 could save lives and buy time for referral and transportation delays. These interventions should be used together when necessary (in cases of shock) and should both decrease blood loss and cause clot formation, so that they can be effective with tranexamic acid. SM holds a faculty position at the University of California, San Francisco, which holds the right to the trademark LifeWrap (one brand of NASG) and has licensed this trademark to the BlueFuzion Group. BlueFuzion Group pays the University of California, San Francisco a royalty of 2·5% for the use of the trademark LifeWrap. All other authors declare no competing interests.